Development of the BR Patent Web System: a platform for the technological prospecting of patents - Nascimento, Tatiana Costa (2022)
Patent BR is a free web system for technological prospecting for patents. Its purpose is to make the strategic information contained in patent documents accessible and uncomplicated in order to popularize technological prospecting for patents and foster innovation in Brazil. The platform performs patent searches, data processing and analysis by generating dynamic graphics in an automated way. Furthermore, it allows the creation of a technological showcase for Brazilian patents and a patent academy for educational purposes. Finally, it is suggested to implement the provision of specialized services through the creation of a Support Center for Technology and Innovation and other technological solutions in patents through the development of a multidisciplinary and multi-institutional research network in the country.